Hubungan Antara Kekuatan Otot Lengan Dengan Kemampuan Pukulan Servis Panjang Dalam Permainan Bulutangkis Pada Siswa SMP Negeri 6 Tondano - Fikram Stion (STIKES Columbia Asia Medan, 2025)
This study aims to determine the relationship between arm muscle strength and the ability to perform long serve shots in badminton among students of SMP Negeri 6 Tondano. The research employed a descriptive correlational method with a quantitative approach. The sample consisted of 15 randomly selected students. The instruments used were a push-up test to measure arm muscle strength and a badminton long serve test to assess the ability to perform long serve shots. The analysis results showed a correlation coefficient (r) of 0.21, with a contribution of 4.41%, indicating a low relationship between the two variables. The t-test results showed that the calculated t-value (tₕ) = 0.79 was smaller than the critical t-value (tₜ) = 2.048, thus the alternative hypothesis was rejected. Therefore, it can be concluded that there is no significant relationship between arm muscle strength and the ability to perform long serve shots among students of SMP Negeri 6 Tondano.